Characterizing social and policy determinants of hospital length of stay among paediatric inpatients with diabetes using linked population-based data - Higgins, Heather; Gupta, Neeru (International Journal of Population Data Science, 2021)
Background Evidence is limited on the non-medical factors influencing hospital length of stay (LOS) among paediatric inpatients with diabetes, notably potential social and policy correlates. This study aimed to characterize the associations of socioeconomic status and health policy environment with diabetes-attributable LOS to help inform accountability monitoring of a provincial comprehensive diabetes strategy aiming to minimize time in hospital among this high-risk population. Data and methods This retrospective population-based study drew on multiple linked administrative and geospatial databases among all children aged 18 and under with a diabetes-related hospitalization in the province of New Brunswick, Canada, during the four-year period following implementation of an insulin pump funding program. Multiple linear regression was used to assess the role of access to the public insulin pump resourcing scheme and relative neighbourhood deprivation as predictors of days spent in acute care, controlling for age, sex, and place of residence. Results Among the paediatric inpatient population (N=386), 21% had accessed social resources made available through the insulin pump funding policy and 42% resided in the most materially deprived neighbourhoods. Diabetes-related hospital stays averaged 3.87 days. Paediatric inpatients having accessed resources through the social insurance policy spent significantly fewer days in hospital (1.34 days less [95% CI: 0.63–2.05]) than those who had not, all else being equal. Observed differences in LOS by neighbourhood socioeconomic deprivation were not found to be statistically significant in the multivariate analysis. Conclusion Findings from this context of universal medical coverage suggested that public policy for supplemental financing of assistive technologies among children with diabetes may be associated with reduced burden to the hospital system. The causes of socioenvironmental disparities in LOS require further investigation to inform interventions to mitigate preventable patient-level variations in hospital-based health outcomes.